2019
DOI: 10.1371/journal.pone.0223384
|View full text |Cite|
|
Sign up to set email alerts
|

Anabolic steroids among resistance training practitioners

Abstract: ObjectiveTo compare the use of anabolic steroids (AS), the motivation to use them, their side effects, the source of information and the form in which AS were obtained, the medical follow-up, and the periodic examinations in resistance training practitioners who are either current or former users of AS.MethodsA prevalence survey was performed in the gyms of the city of Curitiba, including 719 current and former AS users who self-administered a questionnaire. The chi-square and z of proportions (p <0.05) statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(65 reference statements)
2
8
0
Order By: Relevance
“…comparison with reference values and the detection of metabolite in urine, among others. Studies show that the AAS cycle (duration use) [116] can last from 10 to 12 weeks [4,[117][118][119], close to the timeframe of this study. It is important that we evaluated a single, isolated AAS.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…comparison with reference values and the detection of metabolite in urine, among others. Studies show that the AAS cycle (duration use) [116] can last from 10 to 12 weeks [4,[117][118][119], close to the timeframe of this study. It is important that we evaluated a single, isolated AAS.…”
Section: Discussionsupporting
confidence: 72%
“…Despite its therapeutic use, AAS are also indiscriminately used in supraphysiological doses (more than 600 mg/week) [14,15] by many professional or recreational athletes aiming to increase sports performance [16][17][18], rapid gains in lean mass [13,[16][17][18]19], and rapid loss of body fat [10], among other goals. Among several types of AAS, oxandrolone (OX) is one of the most used [23,[23][24][25][26]; high-frequency use (current and former users) made up 45.8% of one sample (n = 719; n = 329) in resistance-training practice (RTP) [27]. OX is used to increase performance [28][29][30][31], as well as to improve net protein balance and lean body mass in patients with serious burns [32,33], Klinefelter Syndrome, metabolic diseases [34], oral pathologies, and HIV [33].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have demonstrated the efficacy of oxandrolone in the treatment of acute catabolic disorders, such as severe burns or severe trauma, and chronic catabolic disorders such as AIDS-associated cachexia or neuromuscular diseases such as Duchenne muscular dystrophy [8]. As well as for therapeutic use, AAS are widely used illicitly by adolescents and athletes, especially by bodybuilders, both for aesthetic uses and as performance enhancers to increase muscle growth and lean body mass, in consideration of their significant anabolic effect [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…2 In this particular case, the patient combined AAS, insulin injections and high-protein diet. Basing on the study from Pereira et al only less than half of interviewed athletes realized the adverse health effects related to anabolic steroids, 3 which may present as various psychiatric symptoms, acne, voice alterations, liver changes, hypertension, arrhythmias, left ventricular hypertrophy, 4,5 decrease of reproductive hormones, potency or gynecomastia. 5,6 Left ventricular hypertrophy was observed in the patient's chest X-ray, which could cause systolic or diastolic function weakening in the future.…”
Section: Resultsmentioning
confidence: 99%